The Role of Gene Expression in Stress Urinary Incontinence: An Integrative Review of Evidence - Iva Miličić; Mislav Mikuš; Adam Vrbanić; Držislav Kalafatić (Medicina, 2023)
Stress urinary incontinence (SUI) is defined as unintentional urine leakage occurring as a consequence of increased intraabdominal pressure due to absent or weak musculus detrusor contractility. It affects postmenopausal women more often than premenopausal and is associated with quality of life (QoL) deterioration. The complex SUI etiology is generally perceived as multifactorial; however, the overall impact of environmental and genetic influences is deficiently understood. In this research report, we have disclosed the upregulation of 15 genes and the downregulation of 2 genes in the genetic etiology of SUI according to the accessible scientific literature. The analytical methods used for the analysis of gene expression in the studies investigated were immunohistochemistry, immunofluorescence staining, PCR, and Western blot. In order to facilitate the interpretation of the results, we have used GeneMania, a potent software which describes genetic expression, co-expression, co-localization, and protein domain similarity. The importance of this review on the genetic pathophysiology of SUI lies in determining susceptibility for targeted genetic therapy, detecting clinical biomarkers, and other possible therapeutic advances. The prevention of SUI with the timely recognition of genetic factors may be important for avoiding invasive operative urogynecological methods.